DISCOVERY OF PULSED gamma-RAYS FROM PSR J0034-0534 WITH THE FERMI LARGE AREA TELESCOPE: A CASE FOR CO-LOCATED RADIO AND gamma-RAY EMISSION REGIONS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
Millisecond pulsars (MSPs) have been firmly established as a class of gamma-ray emitters via the detection of pulsations above 0.1 GeV from eight MSPs by the Fermi Large Area Telescope (LAT). Using 13 months of LAT data, significant gamma-ray pulsations at the radio period have been detected from the MSP PSR J0034-0534, making it the ninth clear MSP detection by the LAT. The gamma-ray light curve shows two peaks separated by 0.274 +/- 0.015 in phase which are very nearly aligned with the radio peaks, a phenomenon seen only in the Crab pulsar until now. The >= 0.1 GeV spectrum of this pulsar is well fit by an exponentially cutoff power law with a cutoff energy of 1.8 +/- 0.6 +/- 0.1 GeV and a photon index of 1.5 +/- 0.2 +/- 0.1, first errors are statistical and second are systematic. The near-alignment of the radio and gamma-ray peaks strongly suggests that the radio and gamma-ray emission regions are co-located and both are the result of caustic formation.
CRIS-Team WoS Importer:2020-01-15